HYBRID PARALLEL ALGORITHM USING MPI AND OPENMP TO SOLVE OIL DISPLACEMENT PROBLEM - Makhmut, E.; Kenzhebek, Е.; Imankulov, Т. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2023)
Recently, modern information technologies are used in many areas of industry, and the use of parallel computing allows to increase the productivity of numerical modeling. In this study, a numerical model of oil displacement was developed using high performance computing technologies. In particular, the process of oil displacement was described using the Buckley-Leverett model. OpenMP, MPI and hybrid (OpenMP+MPI) parallel computing models were considered as high-performance computing technologies. The main goal of this study is to make a comparative analysis of the calculation time and acceleration of parallel algorithms for different technologies. Computational models of parallel algorithms were created and the results were compared.